Pengaruh Kualitas Audit dan Manajemen Laba Terhadap Laporan Keuangan pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2021-2023 (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the effect of audit quality and earnings management on financial statements for banking companies listed on the IDX during the period 2021-2023. The research method used is a quantitative method with an associative approach. The population in this study consists of 47 banking companies listed on the IDX during the period 2021-2023, with a sample size of 81 observational data selected using purposive sampling technique. The data used is secondary data obtained from financial statements or annual financial reports. Data analysis techniques used include descriptive statistical analysis, normality tests, classical assumption tests, and multiple linear regression analysis, as well as hypothesis testing through t-tests and coefficient of determination (R2) tests, with the aid of SPSS version 25. The research results indicate that audit quality (X1) has a positive effect on the accuracy of financial statements, while earnings management (X2) does not have an effect.